(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2023)
Malaysia is a water area that is strategic and rich in natural resources, which is an attraction for foreign fishermen to catch fish. Widespread fishery exploitation by neighbouring countries such as Vietnam has resulted in increasingly limited and declining fishery resources. This study discusses and identifies the factors, modus operandi and implications of the encroachment of foreign fishermen in the waters of the East Coast of Peninsular Malaysia. The results of the study found that there are three main factors of encroaching activities, including the vast geographical location, extinction of fish species, socio-economic needs and ineffective governance. This encroachment is associated with IUU fishing, which is illegal fishing that is unreported and unregulated without obtaining legal permission from a country. There is a provision of the Fisheries Act 1985 (Act 317) on the exclusive fishing rights or fisheries management rights to protect the Malaysian watershed from being encroached. The modus operandi of fishing activities is often carried out during the monsoon season and rough seas, assisted by a syndicate of locals who plan the entry of foreign fishing boats. The implications of IUU activities pose a threat to the security of Malaysia’s maritime waters, affect local fishermen’s sources of income and increase cross-border crime. Keywords: Encroachment, foreign fishermen, waters, modus operandi, IUU, maritime security, Fisheries Act 1985 (Act 317) Full text: PDF